The Implementation of Collaborative Strategy in Teaching based on Virtual Instructor System to Improve Learning Outcomes in Sports Health Education - Febriyanti, Irma; Ridwan, Mochamad (UNIB Press, 2023)
This research aims to improve the quality of learning in Sports Health Education courses using Collaborative Strategy In Teaching Based on the Virtual Instructor System (VIS) for sixth semester students of the Physical Education Study Program, FKIP, Bengkulu University. Virtual Instructor System (VIS) is an application as a place to work well collaboratively. The Virtual Instructor System (VIS) also tells the team during task evaluation how specific the instructions are and will be carried out. This research uses descriptive qualitative, where the practice of adopting the Virtual Instructor System (VIS)-based Collaborative Strategy In Teaching learning approach is described in each context. Where data collection is carried out through test and non-test techniques. As a result, achievement targets were obtained in cycle II with the following details; 15 students or 42% got category A, 17 students or 47% got category B, 4 students or 11% got category C, and none or 0 students got category D. The results of the response questionnaire distributed to students showed the results The final score was 24.61 or an average of 4.1, which means that the category most often chosen by students was agreed. These results show that the implementation of learning in the application of Collaborative Strategy In Teaching for sixth semester students of the Physical Education Study Program, FKIP, Bengkulu University is of interest to students. It not only reaches aspects of knowledge implementation but also increases students' creativity and interest in learning activities.